An Unexpected Etiology of Priapism: Infection‐Related Anti‐Protein S Antibodies. (1st November 2014) - Boissier, Elodie; Durant, Cécile; Vildy, Sophie; Glemain, Pascal; Lakhal, Karim; Graveleau, Julie; Masseau, Agathe; Fouassier, Marc
Abstract: Introduction: In adolescents, the occurrence of priapism is commonly related to sickle cell disease and rarely to other causes. We hereby report a case of priapism due to an acquired protein S (PS) deficiency. Aim: The aim of this study was to describe a young man who developed a priapism with a thrombosis of the corpora cavernosa associated with an anti‐PS antibody (anti‐PS Ab). Methods: One week after the onset of an influenza‐like illness, a young male developed multiple extensive venous thromboses including a thrombosis of the corpora cavernosa causing painful partial priapism. These thromboses along with purpuric lesions with necrotic vesicles of the feet skin were linked to an acquired PS deficiency due to an anti‐PS Ab. The optimal treatment of anti‐PS Ab‐associated thrombosis is debated but we chose to initiate (i) heparin; (ii) corticosteroids; and (iii) plasmapheresis. Results: Even if priapism lasted more than 4 days, a full recovery of erectile function was observed within 3 months. As compared with priapism due to sickle cell disease, which is commonly associated with definitive erectile dysfunction, this favorable outcome is noteworthy. The skin healing was complete only 6 months later. Conclusion: Acquired PS deficiency complicating an infectious disease is a rare, life‐threatening condition, associated with substantial morbidity related to amputations of limbs or digits. This is the first report of priapism due to acquired PS deficiency.